Physically crosslinked KOH impregnated polyvinyl alcohol based alkaline membrane for direct methanol fuel cell - Gupta U.K.; Pramanik H. (My University, 2025)
A polyvinyl alcohol (PVA) based alkaline membrane was developed in the laboratory for use in direct methanol fuel cell (DMFC). The performance of the alkaline PVA membrane, crosslinked by a physical crosslinking method was assessed. The membrane was characterized using water uptake, KOH uptake, ion exchange capacity, and ionic conductivity methods. The anode and cathode electrocatalysts were Pt-Ru (30:15 wt.%)/carbon black (C) and Pt (40 wt.% )/high surface area carbon (CHSA), respectively. A similar electrocatalyst loading in the order of 1 mg/cm2 was used at the anode and cathode. The cell voltage and current density data were recorded for different concentrations of fuel (methanol) and electrolyte (KOH). The optimum conditions for the fuel cell were 2 M methanol mixed in 3 M KOH solution at a flow rate of 2 mL/min with a cathode feed of humidified oxygen at 100 mL/min. The DMFC was operated at 30°C, irrespective of other operating conditions. The maximum open circuit voltage of 0.6 V, current density of 7.71 mA/cm2 at a cell voltage of 0.23 V, and maximum power density of 1.79 mW/cm2 were obtained at the optimum cell condition. The KOH-doped PVA solid electrolyte was successfully tested in a direct methanol fuel cell, which resulted in excellent power density. Single cell test results prove that the physically crosslinked KOH-doped PVA electrolyte could be used as a suitable solid electrolyte in a fuel cell.